Targeting vasoactive intestinal peptide-mediated signaling enhances response to immune checkpoint therapy in pancreatic ductal adenocarcinoma - Sruthi Ravindranathan; Tenzin Passang; Jian-Ming Li; Shuhua Wang; Rohan Dhamsania; Michael Brandon Ware; Mohammad Y. Zaidi; Jingru Zhu; Maria Cardenas; Yuan Liu; Sanjeev Gumber; Brian Robinson; et al. (Nature Communications, 2022)
Poor antitumor response of pancreatic cancer to immunotherapies is a major barrier to effective disease management. Herein we show that pancreatic cancers overexpress vasoactive intestinal peptide, and pharmacological inhibition of its signaling significantly enhances responsiveness of pancreatic ductal adenocarcinoma to immune checkpoint therapy, thus improving overall survival in mouse models.